REKONSTRUKSI PEMIKIRAN HUKUM ISLAM MELALUI INTEGRASI METODE KLASIK DENGAN METODE SAINTIFIK MODERN - Mahsun Mahsun (Al-Ahkam, 2015)
This article discusses methodological thinking about integration deals between classical methods with modern scientific methods in a project of reconstruction of Islamic legal thought. The idea of this paper is motivated by the need for the development of Islamic thought, especially in Islamic law. Philosophically, the real emergence manhaji-eclectic method as a result of integration between the classical methods and modern scientific methods is possible. Implementation of the integration must meet the main prerequisites: first, making al-maṣlaḥah al-'āmmah (public decency) or maqāṣid alsharī’ah as a decisive consideration in seeking a legal aid in three main domains, namely ḍarūriyyah (urgent needs) ḥājiyyah (normal needs), and taḥsīniyyah (complementary needs). The second prerequisite, is the emergence of human consciousness that the classical method will not capable to answer the challenges that change dynamically. While the third, is the willingness of people to change to something new and better, as the implementation of al-muḥāfaẓah ‘alā al-qadīm al-ṣāliḥ wa al-akhdh bi ‘l-jadīd l-aṣlaḥ